Health Care and its Financing in Italy : Issues and Reform Options - Reviglio, Franco (Washington, D.C. : International Monetary Fund, 2000)
In Italy, health care budget ceilings are not effective. The poor control by the central government results in excessive use of expensive inputs, in long waiting lines for medical procedures, and in the emergence of large arrears to suppliers and commercial banks. To fully gain the benefits of its decentralized structure, Italy needs to clarify the rules of the game and strengthen controls on local health authorities. Full fiscal responsibility should be extended to local governments on both the expenditure and revenue sides. The central government should be involved neither in decisions on the services that local governments should supply, nor in their planning and management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet